Hypoxia-Induced Mitogenic Factor: A Multifunctional Protein Involved in Health and Disease - Lv, Moyang; Liu, Wenjuan (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia-induced mitogenic factor (HIMF), also known as resistin-like molecule α (RELMα) or found in inflammatory zone 1 (FIZZ1) is a member of the RELM protein family expressed in mice. It is involved in a plethora of physiological processes, including mitogenesis, angiogenesis, inflammation, and vasoconstriction. HIMF expression can be stimulated under pathological conditions and this plays a critical role in pulmonary, cardiovascular and metabolic disorders. The present review summarizes the molecular characteristics, and the physiological and pathological roles of HIMF in normal and diseased conditions. The potential clinical significance of these findings for human is also discussed.